Reducing Extracellular Ca2+ Induces Adenosine Release via Equilibrative Nucleoside Transporters to Provide Negative Feedback Control of Activity in the Hippocampus - Diez, Rebecca; Richardson, Magnus J. E.; Wall, Mark J. (Frontiers in Neural Circuits, 2017)
Neural circuit activity increases the release of the purine neuromodulator adenosine into the extracellular space leading to A1 receptor activation and negative feedback via membrane hyperpolarisation and inhibition of transmitter release. Adenosine can be released by a number of different mechanisms that include Ca2+ dependent processes such as the exocytosis of ATP. During sustained pathological network activity, ischemia and hypoxia the extracellular concentration of calcium ions (Ca2+) markedly falls, inhibiting exocytosis and potentially reducing adenosine release. However it has been observed that reducing extracellular Ca2+ can induce paradoxical neural activity and can also increase adenosine release. Here we have investigated adenosine signalling and release mechanisms that occur when extracellular Ca2+ is removed. Using electrophysiology and microelectrode biosensor measurements we have found that adenosine is directly released into the extracellular space by the removal of extracellular Ca2+ and controls the induced neural activity via A1 receptor-mediated membrane potential hyperpolarisation. Following Ca2+ removal, adenosine is released via equilibrative nucleoside transporters (ENTs), which when blocked leads to hyper-excitation. We propose that sustained action potential firing following Ca2+ removal leads to hydrolysis of ATP and a build-up of intracellular adenosine which then effluxes into the extracellular space via ENTs.